'Everything was black and white … ': primary school pupils' naive reasoning while situating historical phenomena in time. Issue 1 (2nd January 2019) - de Groot-Reuvekamp, Marjan; Ros, Anje; van Boxtel, Carla
ABSTRACT: This study focuses on problems in pupils' reasoning when they situate historical phenomena in time. The context is the Dutch curriculum with 10 eras and characteristic features, which was implemented to support pupils in orientating themselves in time. Twenty-two pupils aged 6–12 conducted assignments in which they had to place historical phenomena in time. Next to problems that were described in previous studies, problems were identified that related to the names and icons of the 10 eras, which sometimes helped, but also hindered pupils in their reasoning. Awareness of these problems is helpful for teachers, teacher trainers and educational policymakers.